Role of chromosome 3p12–p21 tumour suppressor genes in clear cell renal cell carcinoma: analysis of VHL dependent and VHL independent pathways of tumorigenesis. Issue 3 (1st June 2000) - Martinez, A; Fullwood, P; Kondo, K; Kishida, T; Yao, M; Maher, E R; Latif, F
Abstract : Aims —Chromosome 3p deletions and loss of heterozygosity (LOH) for 3p markers are features of clear cell renal cell carcinoma but are rare in non-clear cell renal cell carcinoma. The VHL tumour suppressor gene, which maps to 3p25, is a major gatekeeper gene for clear cell renal cell carcinoma and is inactivated in most sporadic cases of this disease. However, it has been suggested that inactivation of other 3p tumour suppressor genes might be crucial for clear cell renal cell carcinoma tumorigenesis, with inactivation (VHL negative) and without inactivation (VHL positive) of the VHL tumour suppressor gene. This study set out to investigate the role of non-VHL tumour suppressor genes in VHL negative and VHL positive clear cell renal cell carcinoma. Methods —Eighty two clear cell renal cell carcinomas of known VHL inactivation status were analysed for LOH at polymorphic loci within the candidate crucial regions for chromosome 3p tumour suppressor genes (3p25, LCTSGR1 at 3p21.3, LCTSGR2 at 3p12 and at 3p14.2). Results —Chromosome 3p12–p21 LOH was frequent both in VHL negative and VHL positive clear cell renal cell carcinoma. However, although the frequency of 3p25 LOH in VHL negative clear cell renal cell carcinoma was similar to that at 3p12–p21, VHL positive tumours demonstrated significantly less LOH at 3p25 than at 3p12–p21. Although there was evidence of LOH for clear cell renal cell carcinoma tumour suppressor genes at 3p21, 3p14.2, and 3p12, both in VHL negative and VHL positive tumours, the major clear cell renal cell carcinoma LOH region mapped to 3p21.3, close to the lung cancer tumour suppressor gene region 1 (LCTSGR1). There was no association between tumour VHL status and tumour grade and stage. Conclusions —These findings further indicate that VHL inactivation is not sufficient to initiate clear cell renal cell carcinoma and that loss of a gatekeeper 3p21 tumour suppressor gene is a crucial event for renal cell carcinoma development in both VHL negative and VHL positive clear cell renal cell carcinoma.